Meta Analysis: Relationship of Tuberculosis Patient Contact, Density And Ventilation Area With Tuberculosis Events - Muhammad Riza; Husaini Husaini; Ardik Lahdimawan; Rosihan Adhani; Meitria Syahadatina Noor (Jurnal Berkala Kesehatan, 2021)
Tuberculosis is one of 10 causes of death in the world. In 2018 TB sufferers in Indonesia reached 840 thousand people, the third-highest figure in the world after India and China. The purpose of this study was to analyze the relationship between contact with tuberculosis patients, occupancy density and ventilation area with tuberculosis’ incidence. This study used meta-analysis, the articles’ sources were from Google Scholar, PubMed and DOAJ published from 2011-2020. There were 12 articles that met the conditions for contact-free variables with tuberculosis patients, 12 articles of occupancy density, and 10 articles of ventilation area variable. The results were contacting with tuberculosis patients had 5.93 times more of getting tuberculosis compared to people who had no contact with tuberculosis patients, people who lived in densely populated areas were 2.41 times more getting tuberculosis compared to people living in occupancy that is not crowded, people who live in dwellings with a non-standard ventilation area were 2.14 times more getting tuberculosis when compared to people who live in an area where the ventilation area meets the standard. The conclusion of this study is tuberculosis patient contact, occupancy density, and ventilation area with the incidence of tuberculosis have a significant relationship.